Folate Receptor-Beta Expression as a Diagnostic Target in Human & Rodent Nonalcoholic Steatohepatitis - Lake, April D. (Toxicol Appl Pharmacol, 2019)
INTRODUCTION: Nonalcoholic steatohepatitis (NASH) afflicts 20–36% of individuals with nonalcoholic fatty liver disease (NAFLD). A lipotoxic hepatic environment, altered innate immune signaling and inflammation are defining features of progression to NASH. Activated resident liver macrophages express folate receptor beta (FR-β) which may be an indicator of progression from steatosis to NASH. The goals of this study were to characterize FR-β protein expression in human NAFLD and rodent models of NASH, and demonstrate liver targeting of an FR-β imaging agent to the liver of a rodent NASH model using FR-β. METHODS: Rat liver lysates from methionine choline deficient (MCD) fed rats, high fat diet (HFD) and methionine choline sufficient (MC+) rat controls were analyzed for hepatic FR-β protein. The FR-β-targeted agent, Etarfolatide was injected into MCD and MC+-fed C57BL/6 mice for efficient FastSPECT hepatic imaging. Additionally, FR-β expression across the stages of human NAFLD from normal to NASH was assessed. RESULTS: FastSPECT images show targeting of Etarfolatide to the liver of mice fed 8 weeks of MCD diet but not control-fed mice. The MCD rat model exhibited significantly increased protein expression of hepatic FR-β in contrast to HFD or normal samples. Similarly human liver samples categorized as NASH Fatty or NASH Not Fatty showed elevated FR-β protein when compared to normal liver. FR-β transcript expression levels were elevated across both NASH Fatty and NASH Not Fatty samples. CONCLUSION: The findings in this study indicate that FR-β expression in NASH may be harnessed to target agents directly to the liver.